Issues, Challenges and Problems with Tax Evasion: The Institutional Factors Approach - Mohd Rizal Palil; Marlin Marissa Malek; Abdul Rahim Jaguli (Gadjah Mada International Journal of Business, 2016)
Tax evasion, particularly in developing countries is a debatable issue. Evasion is a disease and needs to be minimized so that the black economy or hidden economy can be mitigated. This paper attempts to reveal the determinants of tax evasion from the institutional perspectives. The objective of this study is to identify the determinants of tax evasion a decade after the introduction of a Self-Assessment System (SAS). Three institutional perspectives of the determinants of tax evasion were examined, namely the probability of being detected, the role of the tax authority and the complexity of the tax system. The results suggested that the complexity of the system, and the probability of being detected had a significant impact on tax evasion. The results of this study could possibly contribute to the body of knowledge in lieu of combating tax evasion, as well as being an input to tax administrators and policymakers into which ways the determinants can affect compliance. The findings also provide an indicator for tax administrators of the relative importance of the tax system in assisting with the design of tax education programs, simplifying tax systems and developing a wider understanding of taxpayers’ behavior.